Social Cognition in Neurodevelopmental Disorders and Epilepsy - Pastorino, Grazia Maria Giovanna; Operto, Francesca Felicia; Padovano, Chiara; Vivenzio, Valentina; Scuoppo, Chiara; Pastorino, Nazareno; Roccella, Michele; Vetri, Luigi; Carotenuto, Marco; Coppola, Giangennaro (Frontiers in Neurology, 2021)
Introduction: The purpose of our study was to perform a comparative analysis of Social Cognition in children and adolescents with epilepsy, Autism Spectrum Disorder (ASD), Specific Learning Disorder (SLD) and in Typical Development (TD) controls. Secondary aim was to relate Social Cognition with some clinical and demographic characteristics. Methods: Our work is a transversal observational study. 179 children and adolescents aged between 6-18 years diagnosed with epilepsy, ASD or SLD and 32 subjects with TD were recruited. All the participants underwent neuropsychological assessment of Emotion Recognition (ER) and Theory of Mind (ToM) skills Results: All three clinical groups performed significantly worse than controls in ER and ToM. The ASD group achieved significantly lower performance than the other groups, instead the scores of SLD and epilepsy groups were comparable. The ER performances are related to non-verbal intelligence only in the group with epilepsy. Conclusion: Children and adolescents with focal epilepsy, SLD or ASD may present deficit of different extent in emotions recognition and ToM, compared with TD peers. These difficulties are more pronounced in individuals with ASD, but an impairment worthy of clinical attention also emerge in individuals with SLD and epilepsy.